Biosphere reserve as a category of natural and reserved fund: justification for creation of the object in the Chornobyl exclusion zone - Бондаренко, О.; Гуцал, О.; Драпалюк, А.; Мовчан, Я.; Потапенко, М. (Man and Environment. Issues of Neoecology)
In this article considered approaches to creation of the object of natural reserve fund at the Chornobyl Polissia, where as a result of the Chornobyl disaster (in 1986), large areas were contaminated by radionuclides, intense economic activity was stopped, settlements were abandoned, the men – resettled. After removal of anthropogenic impact on the ecosystems at territory of Zone formed conditions for the restoration of flora, fauna and habitats. And there is a reason to expect that within 30-50 years at the territory of Zone will form biocenosis the value of which is difficult to assess now. At this article substantiated creation of biosphere reserve due to methodology of the Program «Man and Biosphere» UNESCO and introduction of regulated environmentally reasonable usage.